S16 Remote control: real world effectiveness of virtual, group-delivered speech and language therapy for chronic refractory cough. (11th November 2022) - de Looper, A; Melville, A; Birring, SS; Jolley, CJ; Hull, JH; Selby, J
Abstract : Introduction: Specialist speech and language therapy (SLT) has an established role in the treatment of chronic refractory cough. Therapy delivered in a group format has been shown previously to reduce cough severity1. Attendance in person, however, was interrupted by the coronavirus pandemic. This work reports the effectiveness of a virtual, SLT-led cough therapy group (VCTG). Method: Eligible patients referred between January-June 2022 from two specialist cough clinics were invited to join VCTG. The group comprised of four sessions at weekly intervals, with a review at week 10. Group size ranged from 3–8 patients; sessions were run via Microsoft Teams. Patients were asked to complete a visual analogue scale (VAS) for cough severity (anchored by 'no cough' to 'worst cough ever') and self-belief in controlling their symptoms ('no self-belief' to 'complete self-belief') and the Leicester Cough Questionnaire (LCQ) at weeks 1, 4 and 10. Patients had the opportunity to provide qualitative feedback on their experience in the group. Results: Twenty-eight patients ( n =24 female, 85.7%) aged between 29 and 78 ( M =55) attended VCTG. Fifteen patients completed all outcome measures at weeks 1 and 4; data from week 10 are pending. From weeks 1 to 4, there was a reduction in mean cough severity (63.2% to 36.6%), an increase in mean self-belief (37.3% to 60.2%), and an increase in LCQ scores (9.6 to 12) following group attendance. The predominant theme from qualitative feedback was the value of meeting other people with CRC and not feeling alone. Conclusions: Online delivery of group SLT sessions is effective in improving symptoms of CRC and in facilitating valuable support between group members. Patients felt better equipped to control their cough with reductions in cough severity and in the impact on psychosocial and physical wellbeing. Future work is needed to optimise completion of outcome measures and to examine long-term maintenance of improved symptom control. References: Selby J, Bailey E, Gillies F, Hull JH. Time to re-group: a novel approach to the delivery of speech and language therapy for chronic refractory cough. Thorax 2017;72 :A141.